Revision of the goldenrod-galling Rhopalomyia species (Diptera: Cecidomyiidae) in North America - Dorchin, Netta; Mcevoy, Miles V.; Dowling, Todd A.; Abrahamson, Warren G.; Moore, Joseph G. (Zootaxa, 2009)
Goldenrods (Solidago and Euthamia species) are common herbs in the eastern United States that support a large and diverse community of highly specific gall-inducing insects. The majority of these insects are gall midges, of which 16 described species are bud, leaf, stem, rhizome, or flower-head gallers belonging to the large genus Rhopalomyia Rübsaamen. The present work is a taxonomic revision of the goldenrod-associated Rhopalomyia species, which includes a key to the identification of species based on their galls and host plants and descriptions of diagnostic characters for all species. Rhopalomyia lanceolata Felt is designated as a new synonym for R. lobata Felt, and R. albipennis Felt and R. carolina Felt are designated as new synonyms for R. solidaginis Loew. Neotypes are designated for R. hirtipes Osten Sacken and R. solidaginis, and two new species are described—R. gina Dorchin n.sp. and R. guttata Dorchin n.sp. Descriptions include illustrations of galls, male and female morphological characters, and the first description of pupae, where available. New or additional detailed information is also provided on gall structure, phenology, and life history of the gall midges.